New insights into the manual activities of individuals from the Phaleron cemetery (Archaic Athens, Greece). (July 2021) - Karakostis, Fotios Alexandros; Buikstra, Jane E.; Prevedorou, Eleanna; Hannigan, Elizabeth M.; Hotaling, Jessica; Hotz, Gerhard; Liedl, Hannah; Moraitis, Konstantinos; Siek, Thomas J.; Waltenberger, Lukas; Widrick, Kerri J.; Harvati, Katerina
Abstract: Until the early 5th century BC, Phaleron Bay was the main port of ancient Athens (Greece). On its shore, archaeologists have discovered one of the largest known cemeteries in ancient Greece, including a range of burial forms, simple pits, cremations, larnaces (clay tubs), and series of burials of male individuals who appear to have died violent deaths, referred to here as "atypical burials". Reconstructing the osteobiographies of these individuals will help create a deeper understanding of the socio-political conditions preceding the rise of Classical Athens. Here, we assess the habitual manual behavior of the people of Archaic Phaleron (ca. 7th – 6th cent. BC), relying on a new and precise three-dimensional method for reconstructing physical activity based on hand muscle attachment sites. This approach has been recently validated on laboratory animal samples as well as on recent human skeletons with a detailed level of long-term occupational documentation (i.e., the mid-19th century Basel Spitalfriedhof sample). Our Phaleron sample consists of 48 adequately preserved hand skeletons, of which 14 correspond to atypical burials. Our results identified consistent differences in habitual manual behaviors between atypical burials and the rest. The former present a distinctive power-grasping tendency in most skeletons, which was significantly less represented in the latter (p-values of <0.01 and 0.03). Based on a comparison with the uniquely documented Basel sample (45 individuals), this entheseal pattern of the atypical burials was exclusively found in long-term heavy manual laborers. These findings reveal an important activity difference between burials typical for the Phaleron cemetery and atypical burials, suggesting that the latter were likely involved in distinctive, strenuous manual activities. The results of this pilot study comprise an important first step towards reconstructing the identity of these human skeletal remains. Future research can further elucidate the occupational profiles of these individuals through the discovery of additional well-preserved hand skeletons and by extending our analyses to other anatomical regions. Highlights: We reconstructed manual activity in individuals from Archaic Athens (Phaleron bay). Individuals that seem to have died violently show marked power-grasping patterns. These patterns were only similar to those of documented heavy manual laborers. The manual activities of most other burials were consistently less strenuous.